Pengaruh Perceived Ease of Use, Perceived Usefulness, dan Perceived Enjoyment terhadap Continuance Intention Pengguna Aplikasi Bestee Ku - Arifani, Iqnes Septya (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
This study aims to analyze the influence of perceived ease of use, perceived usefulness, and perceived enjoyment on the continuance intention of Bestee Ku application users, both partially and simultaneously. A quantitative approach was employed using explanatory research, involving 120 respondents selected through purposive sampling. Data were collected via questionnaires and analyzed using multiple linear regression with the assistance of SPSS 27. The results indicate that all three independent variables have a positive and significant effect on continuance intention, both partially and simultaneously. These findings suggest that application developers should optimize ease of use, perceived benefits, and enjoyable user experiences to enhance user continuance. Keywords: perceived ease of use, perceived usefulness, perceived enjoyment, continuance intention.